Pengaruh Interval Pemberian Air Dan Jenis Pupuk Kandang Terhadap Pertumbuhan Dan Hasil Tanaman Kacang Hijau (Vigna Radiata L.) - Suhartono Suhartono; Achmad Djunaedy; Edy Suryono; Ali Bekti Widodo (Rekayasa, 2021)
This study aims to determine the effect of water application intervals and the type of drum fertilizer on the growth and yield of mung bean (Vigna radiata L.), This research was conducted in the greenhouse of Agrotechnology Study Program, Faculty of Agriculture, Trunojoyo University, Madura. The research design used a factorial Completely Randomized Design (CRD) which consisted of 2 factors, factor I, the water supply interval consisted of four levels, namely A1 (1 once a day), A2 (2 once a day), A3 (3 once a day), A4 (4 days). very). Factor II type of manure consists of two levels, namely P1 (cow manure) and P2 (goat manure). The results showed that the water treatment interval had a significant effect on plant height parameters at all ages of observation and leaf number parameters at 27 and 39 DAP. The highest value was obtained by treatment A1. Treatment The type of manure only had a significant effect on the number of leaves at 39 DAP. There was an interaction between the treatment interval of water application and the type of manure on the parameters of wet weight, dry weight, number of pods per plant and seed weight per plant and the best treatment was P1A4.